Polish Theatre in the Time of War (1939–1945). Fight—Will to Survive—Losses—Legacy - Braun, Kazimierz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
During World War II Polish theatre people took an active part in the fight with both Germany and the Soviet Union. Several of them fought with a weapon in hand as officers and soldiers of Polish armies in the September 1939 campaign, later as combatants of the Home Army (AK), and also within Polish armed forces fighting abroad. Many more fought with a weapon of the word. While boycotting German sponsored stages in the General Government, they created the whole network of small underground theatre groups. Two major centers of this activity were Warsaw, where the Clandestine Theatre Council (Bohdan Korzeniewski, Leon Schiller, Edmund Wierciński and others) organized and sponsored underground theatre productions and acting studios, and Kraków with The Rhapsodic Theatre (led by Mieczysław Kotlarczyk), The Independent Theatre (led by Tadeusz Kantor), and a circle of artists and apprentices gathered around Juliusz Osterwa, who frequently gave one-man shows. Productions were also prepared in German oflags and concentration camps. The great actor Stefan Jaracz performed for fellow inmates in Auschwitz, Zofia Rysiówna in Ravensbrück, and Roman Niewiarowicz in Dachau. Such productions were recorded also in Soviet camps (gulag system). Soldier theatres were organized at the Gen. Anders Second Corp, then also at the Polish forces under Soviet command. Losses of Polish theatre due to the war were staggering. In terms of material losses, The National Theatre in Warsaw was bombed by the Lufwaffe on September 19, 1939, and eventually Poland lost about 70% of theatre buildings standing in August 1939, plus their libraries, sets and costumes magazines, etc. In terms of human losses, about 300 theatre professionals died (out of about 2000 in 1939). Some were killed in military actions, some murdered in either German or Soviet camps. The losses in the spiritual domain were uncountable. Theatre artists were deprived of the possibility to perform, thus executing their profession and vocation. Theatre spectators were left without their artistic nourishment. The struggles, sacrifices, and deeds of the war-time Polish theatre had a profound influence on the history of Polish theatre of the second half of the 20th century. They were not only an important element of the nation’s war-effort, but—indirectly— contributed to the restoration of Poland’s freedom at the end of the 20th century.

W czasach II wojny światowej polscy ludzie teatru wzięli aktywny udział w walce zarówno z Niemcami, jak i Związkiem Sowieckim. Wielu z nich walczyło z bronią w ręku w Kampanii Wrześniowej 1939 r., a potem jako żołnierze Armii Krajowej. Niektórzy służyli w Polskich Siłach Zbrojnych za granicami kraju. Prawie całe środowisko teatralne (z małymi wyjątkami) walczyło natomiast bronią słowa. Bojkotując przedstawienia oficjalnie dozwolone przez okupanta niemieckiego i starając się nie poddać zarządzeniom okupanta sowieckiego, ludzie teatru stworzyli sieć teatru podziemnego na terenie całego kraju. W Warszawie utworzono Tajną Radę Teatralną (Bohdan Korzeniewski, Leon Schiller, Edmund Wierciński i inni), grano tajne przedstawienia i prowadzono tajne studia aktorskie. W Krakowie działały podziemnie: Teatr Rapsodyczny (prowadzony przez Mieczysława Kotlarczyka), Teatr Niezależny (stworzony przez Tadeusza Kantora), oraz środowisko skupione wokół Juliusza Osterwy, który dawał przedstawienia „teatru jednego aktora”, uczył aktorstwa, prowadził kursy w seminariach duchownych oraz spisał plany powołania dwóch zakonów teatralnych, zwanych „Genezja” i „Dal”. Przedstawienia były również przygotowywane w niemieckich oflagach oraz obozach koncentracyjnych. Stefan Jaracz występował dla współwięźniów w Auschwitz, Zofia Rysiówna w Ravensbrück, Roman Niewiarowicz w Dachau. Podobne, choć rzadsze przedstawienia zanotowano także w sowieckich obozach dla oficerów i w łagrach. Teatry grające dla żołnierzy oraz polskich cywilów powstały w 2 Korpusie gen. Władysława Andersa i innych polskich formacjach wojskowych na Zachodzie, a także przy polskim wojsku pod komendą sowiecką. Straty materialne teatru polskiego spowodowane wojną były ogromne. Teatr Narodowy w Warszawie został zbombardowany przez Luftwaffe 19 września 1939 r. Ogólnie Polska straciła ok. 70% budynków teatralnych oraz teatralne biblioteki, magazyny dekoracji i kostiumów itp. Straty ludzkie wyniosły ok. 300 zawodowych ludzi teatru (na ok. 2000 w 1939 r.). Niektórzy padli w walkach (jak Ludwik Berger). Inni zostali zamordowanych w więzieniach (jak Nina Veight) i obozach niemieckich ( jak Mieczysław Węgrzyn) lub sowieckich ( jak Eugeniusz Bodo). Straty duchowe są nie do policzenia: artyści zostali pozbawieni możliwości realizowania swego powołania i praktykowania zawodu, a widzowie strawy duchowej i przeżyć artystycznych. Walka, ofiary, działania i plany ludzi teatru czasu wojny miały głęboki wpływ na historię polskiego teatru w II połowie XX w. Przyczyniły się – choć nie bezpośrednio – do przechowania polskiej tożsamości narodowej w czasach rządów komunistycznych i do odzyskania przez Polskę niepodległości w końcu XX w.
Teatr polski w czasach II wojny światowej (1939–1945). Walka – wola przetrwania – straty – spuścizna
The article is an extended version of the paper delivered at the conference “Poland First to Fight” in Washington D.C., November 18, 2019.
Keywords: underground theatre; boycott; soldier’s theatres; material losses; human losses; spiritual losses; legacy; teatr podziemny; bojkot; teatry żołnierskie; straty materialne; straty ludzkie; straty duchowe; spuścizna